위암 수술 후 간호에 대한 Debriefing for Meaningful 적용 시뮬레이션 교육의 효과 - 김미강(Mi Kang Kim); 임현숙(Hyun Sook Lim); 김유미(Yu Mi Kim); 이현예(Hyun Ye Lee) (한국간호연구학회지, 2023)
Purpose : Debriefing is essential for the simulation practice, but the educational varies depending on the debriefing guide. The purpose of this study is to present the effects of attempting debriefing for meaningful learning (DML) for the simulation practice on the critical thinking disposition, problem-solving processes, learning self-efficacy and debriefing experience scale. Methods : This study is based on the single group pre-post test experimental design study, with 58 fourth graders of nursing students were targeted. The application of DML for the simulation practice was conducted for 7 weeks on the subject of nursing care after gastric cancer surgery was completed from May 8 to June 16, 2023. The collected data were analyzed using SPSS 27.0 through the frequency, percentage, mean, standard deviation and paired t-test. Results : After DML, the results present that there were significant differences in the problem-solving processes(t＝-2.79, p＝.007) and learning self-efficacy(t＝-3.90, p＜.001), while the critical thinking disposition(t＝-1.61, p＝.111) demonstrated no significant differences. Conclusion : In the simulation-based education, debriefing with DML can be used as an effective strategy, and the comparative and repetitive studies using other debriefing will be needed in the future. KCI Citation Count: 0